PREDICTION OF CONVERGENCE VALUES IN SHALLOW TUNNELS WITH VARIOUS SUPPORT SYSTEMS FOR VERY GOOD ROCK MASS CLASS (RMR= 80 - 100) - Geraldo Manalu, Michael
Convergent value prediction and support determination are challenges in planning shallow tunnel construction even though both are fundamental aspects to planning a tunnel that is stable, safe, and can work as intended. This research focuses on providing a solution to determining the convergent value of the excellent rock mass class based on the relationship between the characteristics of the support type and the depth variation so that the convergent determination can be determined quickly through the output in this research. In addition, this research also analyzes the capacity and capability of the support through the P-M Diagram (EN 1992-1-1) so that recommendations can be obtained for the type of support that can be used in depth variations of 10 m to 60 m. The support system used is a typical type of support system on a two-way road (medium section tunnel) from JSCE guidelines, 2016. Curves were obtained showing the strain values based on the type of support used at various depths. The largest convergent value was obtained at a depth of 60 m with suppport type 1 of 2.26 cm with a strain value of 0.179%. Meanwhile, the recommendation for a stable support type for all depths is support type 2.